SUSTAINABLE CONSUMPTION ACCORDING TO SUSTAINABLE BEHAVIOR’S PILLARS: A case study of the SIRGAZ consumer in Constantine - NECIB, Chahrazed; MERDAOUI, Kamel (Journal of Human Sciences, 2020)
The aim of this study is to describe the realities of sustainable consumption based on sustainable behaviors of SIRGAZ’s consumers. The underpinnings of these behaviors, mainly Pro-Ecologic, Frugal, Altruistic and Equitable behaviors, are analysed. Data collection was undertaken through a Questionnaire that was distributed to a sample of 386 SIRGAZ consumers in three different stations located in Constantine region. We used Statistical Package for the Social Sciences (spss) to analyse the data and generate results. In conclusion, the sample has shown a positive response to sustainable consumption by behaving in accordance to the standards of sustainable behaviors.